Ongoing activities and prospects related to welding technology at Laprosolda-Brazil - Louriel O. Vilarinho; Laura O. Vilarinho (Автоматическая сварка, 2013)
An overview of Laprosolda activities in research, development and innovation of welding processes is presented within three main areas: fundamentals, instrumentation and application. Since the group philosophy aims to develop different welding processes, in this work three cases are presented to illustrate these areas. The first one deals with the measurement of heat input for derivative arc-welding processes. The second case shows embedded systems developed for arc-welding monitoring and control. The last one presents the evaluation of conventional and controlled short-circuit GMAW processes for pipe welding. The objective is to present the ongoing activities and prospects related to welding technology within Laprosolda group.